Metaphase karyotypes of Anopheles paraliae (Diptera: Culicidae) in Thailand and evidence to support five cytological races - K. Taai (2018)
Sixteen isoline colonies of Anopheles paraliae were established from wild-caught females collected from cow-baited traps at 4 locations in Thailand. They showed 3 types of X (X1, X2, X3) and 5 types of Y (Y1, Y2, Y3, Y4, Y5) chromosomes based on the number and amount of major block(s) of heterochromatin present in the heterochromatic arm, and were designated as Forms A (X3, Y1), B (X1, X2, X3, Y2), C (X3, Y3), D (X1, X2, X3, Y4) and E (X3, Y5). Form A was found in Songkhla Province, Form B was obtained in Ratchaburi, Nakhon Si Thammarat and Songkhla Provinces, Form C was acquired in Chanthaburi Province, Form D was recovered in Ratchaburi and Songkhla Provinces, and Form E was encountered in Ratchaburi Province. Hybridization experiments among the 7 isoline colonies, which represented the 5 karyotypic forms of An. paraliae, revealed genetic compatibility in providing viable progenies and synaptic salivary gland polytene chromosomes through F2-generations, and thus suggest the conspecific nature of these karyotypic forms. These results were supported by the very low intraspecific sequence divergence (mean genetic distance = 0.000-0.002) of the nucleotide sequences in ribosomal DNA (ITS2) and mitochondrial DNA (COI and COII) of the 5 forms.